2019
DOI: 10.1038/s41598-019-40925-8
|View full text |Cite
|
Sign up to set email alerts
|

Memantine prodrug as a new agent for Alzheimer’s Disease

Abstract: Hydrogen sulphide has recently drawn much attention due to its potent anti-inflammatory and neuroprotective roles in brain functions. The purpose of the current study was to exploit these beneficial properties of H2S to design a new agent for the treatment of Alzheimer’s disease (AD). To pursue our aims, we replaced the free amine group of memantine with an isothiocyanate functionality as a putative H2S-donor moiety. The new chemical entity, named memit, was then tested in vitro to determine whether it retains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 61 publications
(73 reference statements)
2
24
0
Order By: Relevance
“…In this section, we review studies reported in the recent chemical and biological literature on the miscellaneous memantine derivatives for which AD neuroprotective activity derived by merging two pharmacophores is claimed, but which lie outside the hybrid series described in the other paragraphs of this review. In this regard, a lot of efforts have been made over the years to enhance memantine potency, synthesizing double-acting prodrug or targeting the second region of the same receptor to increase its efficacy [ 6 , 63 ]. Otherwise, merging two well-known NMDAR antagonists has been exploited as a strategy to obtain more efficient channel blockers with potential further clinical applications [ 64 ].…”
Section: Miscellaneous Memantine Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we review studies reported in the recent chemical and biological literature on the miscellaneous memantine derivatives for which AD neuroprotective activity derived by merging two pharmacophores is claimed, but which lie outside the hybrid series described in the other paragraphs of this review. In this regard, a lot of efforts have been made over the years to enhance memantine potency, synthesizing double-acting prodrug or targeting the second region of the same receptor to increase its efficacy [ 6 , 63 ]. Otherwise, merging two well-known NMDAR antagonists has been exploited as a strategy to obtain more efficient channel blockers with potential further clinical applications [ 64 ].…”
Section: Miscellaneous Memantine Derivativesmentioning
confidence: 99%
“…Particularly, H 2 S combines neuroprotection, antinflammatory and antiapoptotic activities to NMDAR-modulation ability both directly, with sulfhydration of critical cysteine residues, and indirectly, through regulation of intracellular calcium concentration [ 72 , 73 ]. On this basis, the interesting biological outputs of compound 18 , an H 2 S-releasing memantine derivative by Sestito and coworkers, can open a range of possibilities for new MTDL campaign [ 63 ]. Compound 18 bears an isothiocyanate moiety as H 2 S-donating moiety, replacing the characteristic free amino group of memantine ( Figure 11 ).…”
Section: Miscellaneous Memantine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 is a nuclear factor responsible for promoting the expression of multiple antioxidant genes and preventing oxidative damage. Such a mechanism of action has been described also for synthetic isothiocyanates whose H 2 S donor profile has been widely described (Citi, Corvino, et al, 2020;Citi et al, 2014Citi et al, , 2019Martelli, Piragine, et al, 2020;Martelli et al, 2014;Prawan et al, 2009;Sestito, Daniele, et al, 2019;Sestito, Pruccoli, et al, 2019;Testai et al, 2016). Anethole dithiolethione, another H 2 S donor, has been widely used as H 2 S donor or as a moiety for the development of H 2 S-releasing hybrid drugs, including non-steroidal anti-inflammatory agents, such as H 2 S-aspirin and H 2 S-diclofenac.…”
Section: H 2 S In Inflammatory Lung Diseasesmentioning
confidence: 97%
“…FDA-approved drugs, including Aricept (donepezil) and Razadyne (galantamine), both of which are cholinesterase inhibitors, prevent memory deficits, but cause side effects such as nausea, vomiting, and muscle cramps [7]. Other agents include minocycline, a tetracycline antibiotic that targets neuroinflammation in AD [8], and memantine, an N-methyl-D-aspartate (NMDA) receptor antagonist that attenuates damage caused by reactive oxygen species (ROS) in the brain [9]. Although mitochondrial dysfunction is a causative factor in memory deficits in AD [3], how mitochondrial modulation by natural compounds alters the expression of key synaptic proteins is not known.…”
Section: Introductionmentioning
confidence: 99%